Computer as components principles of embedded computing system design - Wolf, Marilyn (United States Elsevier, 2023)
This book attemptsto capture some of the basic principles and techniques of this new discipline of embedded computing. Certain challenges of embedded computing are well known in the desktop computing world.
Keywords: Cong nghệ Thông tin